2015
DOI: 10.1002/mc.22430
|View full text |Cite
|
Sign up to set email alerts
|

Reduced SLC27A2 induces cisplatin resistance in lung cancer stem cells by negatively regulating Bmi1‐ABCG2 signaling

Abstract: Platinum-based chemotherapies have long been used as a standard treatment in non-small cell lung cancer (NSCLC). However, cisplatin resistance is a major problem that restricts the use of cisplatin. Lung cancer stem cells (LCSCs) represent a subpopulation that is responsible for chemo-resistance. We aim to investigate the biological function of SLC27A2 and its underlying mechanisms in regulating chemo-resistance to cisplatin in LCSCs. Here, our findings testified that CD166 cells which were derived from fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…In addition, the enrichment of CSCs population were also reported in recent study, whereby the subpopulation of A549 and H2170 with markers CD166 + /EpCAM + showed higher expression upon cisplatin treatment as comparing to basal expression (99). In another study of NSCLC, the CD166 + cells with strong CSCs characteristics also were resistant when exposed to cisplatin drug (125). Furthermore, CSCs can adopt in quiescent state where it resist any cytotoxic insult (126) due to high expression of Bcl-2/Bcl-XL that function in mitochondrial ATP/ADP exchange as to prevent apoptosis which probably contributes to resistant of CSCs upon chemotherapy (127).…”
Section: Challenges In Lung Cscsmentioning
confidence: 99%
“…In addition, the enrichment of CSCs population were also reported in recent study, whereby the subpopulation of A549 and H2170 with markers CD166 + /EpCAM + showed higher expression upon cisplatin treatment as comparing to basal expression (99). In another study of NSCLC, the CD166 + cells with strong CSCs characteristics also were resistant when exposed to cisplatin drug (125). Furthermore, CSCs can adopt in quiescent state where it resist any cytotoxic insult (126) due to high expression of Bcl-2/Bcl-XL that function in mitochondrial ATP/ADP exchange as to prevent apoptosis which probably contributes to resistant of CSCs upon chemotherapy (127).…”
Section: Challenges In Lung Cscsmentioning
confidence: 99%
“…Ovarian cancer cells which were resistant against cisplatin showed also a lower expression of these both genes [51]. Su et al increased the expression of SLC27A2 in lung cancer stem cells and could sensitize these cells against cisplatin [52]. Changes in genes which regulated DNA repair pathways were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…CDDP is a platinum chemotherapeutic agent and is widely used for the treatment of lung cancer (17). DNA is the primary target of CDDP; CDDP-induced DNA damage results in characteristic cellular changes, including the inhibition of DNA synthesis, suppression of RNA transcription, effects on the cell cycle, and the therapeutically beneficial process of apoptosis (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%